Phytochemical Study of Steroidal Sapogenin â€œTigogeninâ€ Present in the Leaves of Yucca aloifolia Cultivated in Iraq - M.Ibrahem, Nabaa; J. Awad, Zainab (Iraqi Journal of Pharmaceutical Sciences, 2017)
This study detects the presence of the most important steroidal sapogenin â€œTigogeninâ€ in the leaves of Yucca aloifolia widely cultivated in Iraq. The absence of any study concerning the Tigogenin content of this medicinal plant in Iraq, and the industrial importance of Tigogenin depending on its role as a precursor in the synthesis of some steroidal drugs, acquired this study its value. This study concerned with extraction, identification, isolation, and purification of Tigogenin from the leaves of Yucca aloifolia. Extraction of this compound was carried out using two methods. Identification of this compound was done using thin layer chromatography (TLC) where different solvent systems had been tried. Libermann â€“ Burchard reagent was used for detection. This identification was further augmented by using high performance liquid chromatography (HPLC) and then this steroidal saponin was isolated and purified. The identification of isolated Tigogenin was carried out using melting point (M.P.), Thin layer chromatography (TLC), infrared spectroscopy (IR) and High performance liquid chromatography (HPLC) . This study confirms the presence of Tigogenin in the leaves of Yucca aloifolia cultivated in Iraq. Also the result of this study showed that the second extraction method was the best, because the amount of both extract and Tigogenin were higher than one extraction method.Key words : Yucca aloifolia , Steroidal saponin , "Tigogenin"